Why social status matters for understanding the interrelationships between testosterone, economic risk‐taking, and gender. Issue 3 (March 2017) - Fisk, Susan Rebecca; Miller, Brennan J.; Overton, Jon
Abstract: We conduct an extensive review of the literature on testosterone and economic risk‐taking behavior. In sum, there is evidence of a positive association between testosterone and economic risk taking, although it is unlikely to be a strong association given the abundance of null results. However, we argue that the existing literature may overstate the causal effects of testosterone on economic risk taking (or even report a spurious correlation) because this research has not considered the potentially confounding role of social status. Status could concurrently influence both testosterone and economic risk taking, given that testosterone is a social hormone with a reciprocal relationship with social status, and social status has been found to drive risk‐taking behavior. We also argue against using findings from this literature to make gender essentialist claims, primarily because social phenomena influence the size—and existence—of gender differences in economic risk‐taking behavior. We conclude with suggestions for future research.